2015
DOI: 10.4081/jphr.2015.376
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Parent Use of New Technologies for Health Communication: A Study in An Urban Latino Community

Abstract: BackgroundMobile communication technologies provide novel opportunities to support clinic-based health initiatives. Adoption of technologies for daily use and for health communication can differ between communities, depending upon demographic and cultural characteristics.Design and methodsA survey was administered in adolescent primary care and subspecialty clinics to assess parent-adolescent preferences in use of mobile technologies and social media to support provider-patient communication in an urban Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Similarly, Smaldone et al (2015) surveyed urban, underserved Latino adolescents about their mobile technologies and social media use and found that most youth lacked an interest in using social media for health communication despite the medium's widespread use among the population (Smaldone et al, 2015). Respondents who were foreign born were less likely to be interested in using social media for health communication than U.S. born Latinos (Smaldone et al, 2015). Our findings suggest that the content and format of social media health communication matters.…”
Section: Changes In Pyd Constructsmentioning
confidence: 72%
See 2 more Smart Citations
“…Similarly, Smaldone et al (2015) surveyed urban, underserved Latino adolescents about their mobile technologies and social media use and found that most youth lacked an interest in using social media for health communication despite the medium's widespread use among the population (Smaldone et al, 2015). Respondents who were foreign born were less likely to be interested in using social media for health communication than U.S. born Latinos (Smaldone et al, 2015). Our findings suggest that the content and format of social media health communication matters.…”
Section: Changes In Pyd Constructsmentioning
confidence: 72%
“…In a study of ninth-and tenth-grade, self-identifying Latino adolescents from public high schools in Maryland, recent immigrants (within the last three years) and Spanish-dominant respondents had significantly less access and less frequent use of social media (Vyas, Landry, Schnider, Rojas, & Wood, 2012). Similarly, Smaldone et al (2015) surveyed urban, underserved Latino adolescents about their mobile technologies and social media use and found that most youth lacked an interest in using social media for health communication despite the medium's widespread use among the population (Smaldone et al, 2015). Respondents who were foreign born were less likely to be interested in using social media for health communication than U.S. born Latinos (Smaldone et al, 2015).…”
Section: Changes In Pyd Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Texting health messages can be an effective way to send reminders from professionals to parents [63] and youth [64, 65] and is well accepted in our community [66]. Systematic reviews and meta-analyses of interventions to improve adherence among youth affected by chronic illness [67, 68] demonstrate the added value of multi-component interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the use of bidirectional SMS text messaging with caregivers to enhance adolescents’ receipt of vaccine and well-care services improved adolescents’ utilization of both services [22], suggesting that caregiver involvement in adolescent-focused mHealth interventions may also be effective in improving other outcomes (eg, engagement in mental health treatment). Studies show that only some, but not all, caregivers are ready for electronic messaging support for health care [23] and that depending on caregiver race (eg, Latino), socioeconomic status (eg, low), and age (eg, younger), SMS text messaging may be more or less appealing as a tool for their adolescent’s health care engagement [19,24].…”
Section: Introductionmentioning
confidence: 99%